2013
DOI: 10.1128/jvi.03460-12
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Kaposi's Sarcoma-Associated Herpesvirus Processivity Factor ORF59 by a Viral Kinase Modulates Its Ability To Associate with RTA and ori Lyt

Abstract: ORF59 of Kaposi's sarcoma-associated herpesvirus (KSHV) plays an essential role in viral lytic replication by providing DNA processivity activity to the viral DNA polymerase (ORF9). ORF59 forms a homodimer in the cytoplasm and binds and translocates ORF9 into the nucleus, where it secures ORF9 to the origin of lytic DNA replication (oriLyt) in order to synthesize long DNA fragments during replication. ORF59 binds to oriLyt through an immediate early protein, replication and transcription activator (RTA). Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 48 publications
(72 reference statements)
2
32
0
Order By: Relevance
“…(ii) ORF36 is critical for efficient viral DNA synthesis. This notion is consistent with recent work showing that ORF36 can phosphorylate the KSHV processivity factor (PF-8, encoded by ORF59) and that ablation of these phosphorylation sites on PF-8 impairs viral particle production (19). (iii) ORF36 is required for packaging of newly assembled viral particles.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…(ii) ORF36 is critical for efficient viral DNA synthesis. This notion is consistent with recent work showing that ORF36 can phosphorylate the KSHV processivity factor (PF-8, encoded by ORF59) and that ablation of these phosphorylation sites on PF-8 impairs viral particle production (19). (iii) ORF36 is required for packaging of newly assembled viral particles.…”
Section: Discussionsupporting
confidence: 80%
“…Since then, several viral and cellular proteins have been reported to be phosphorylated by ORF36. These include MKK4/7 (15), KSHV K8/K-bZIP (16), Kruppel-associated box domain-associated protein-1 (KAP-1/TRIM28) (17), retinoblastoma (Rb) (12), lamin A/C (12), histone H3 (18), and KSHV ORF59/PF-8 (19). However, compared to its homologs in HSV-1 (UL13), HCMV (UL97), and EBV (BGLF4), relatively little is known regarding the functional roles of KSHV ORF36 during viral lytic replication.…”
mentioning
confidence: 99%
“…However, using a model of primary lytic replication, we have shown a direct correlation between the expression of ORF59, the induction of the lytic program of replication, and the production of infectious virions of a primate homolog of KSHV (33). Furthermore, previous studies have shown that an ORF59 deletion mutant of KSHV is defective in virion production, substantiating the critical role of ORF59 in the lytic cycle of replication (34).…”
supporting
confidence: 65%
“…KSHV ORF59 encodes viral processivity factor 8 (PF-8), which assists viral DNA polymerase with DNA processivity activity and plays an essential role in virus genome replication (13)(14)(15). PF-8 expression and function are RTA dependent in forming the replication complex (13)(14)(15)(25)(26)(27), while PF-8's activity and expression are regulated by a viral kinase (ORF36) and ORF57, respectively (16)(17)(18). In addition, PF-8 interacts with Ku70 and Ku86, impairing nonhomologous end joining during lytic replication (34).…”
Section: Discussionmentioning
confidence: 99%
“…KSHV PF-8 is known to play an essential role in virus genome replication by translocating viral DNA polymerase into the nucleus and assisting it with its DNA processivity activity (13)(14)(15). Meanwhile, PF-8 requires RTA for its expression and binding to oriLyt to form the replication complex (16)(17)(18). Our finding that PARP-1 degradation by PF-8 further enhanced RTA-mediated transactivation suggests an intricate feed-forward loop of the lytic replication of the virus.…”
mentioning
confidence: 99%